Maternal exposure to hurricane destruction and fetal mortality. Issue 8 (8th May 2014) - Zahran, Sammy; Breunig, Ian M; Link, Bruce G; Snodgrass, Jeffrey G; Weiler, Stephan; Mielke, Howard W
Abstract : Background: The majority of research documenting the public health impacts of natural disasters focuses on the well-being of adults and their living children. Negative effects may also occur in the unborn, exposed to disaster stressors when critical organ systems are developing and when the consequences of exposure are large. Methods: We exploit spatial and temporal variation in hurricane behaviour as a quasi-experimental design to assess whether fetal death is dose-responsive in the extent of hurricane damage. Data on births and fetal deaths are merged with Parish-level housing wreckage data. Fetal outcomes are regressed on housing wreckage adjusting for the maternal, fetal, placental and other risk factors. The average causal effect of maternal exposure to hurricane destruction is captured by difference-in-differences analyses. Results: The adjusted odds of fetal death are 1.40 (1.07–1.83) and 2.37 (1.684–3.327) times higher in parishes suffering 10–50% and >50% wreckage to housing stock, respectively. For every 1% increase in the destruction of housing stock, we observe a 1.7% (1.1–2.4%) increase in fetal death. Of the 410 officially recorded fetal deaths in these parishes, between 117 and 205 may be attributable to hurricane destruction and postdisaster disorder. The estimated fetal death toll is 17.4–30.6% of the human death toll. Conclusions: The destruction caused by Hurricanes Katrina and Rita imposed significant measurable losses in terms of fetal death. Postdisaster migratory dynamics suggest that the reported effects of maternal exposure to hurricane destruction on fetal death may be conservative.